HIGH SCHOOL STUDENTS' ALGEBRAIC THINKING ABILITY ON ETHNOMATHEMATICS-BASED THREE-VARIABLE LINEAR EQUATION SYSTEM PROBLEMS - Sugiarni, Rani; Iqlima Ridzikia Hidayat, Raishya; Komala, Elsa; Saniah, Lia (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
Algebraic thinking ability is a fairly important ability that must be possessed by students, but in working on test questions there are still some mistakes made by students. Therefore, this study aims to find out what the most mistakes made by students in solving the algebraic thinking ability test refer to Newman's Error Analysis theory and also to find out what factors influence student errors in solving the algebraic thinking test. The research was conducted at public high schools in Cianjur in the even semester of the 2021/2022 academic year. Using a quantitative approach with the type of research conducted is descriptive. The algebraic thinking ability test instrument given as many as 3 questions to 29 students as research subjects within 60 minutes in addition to the test, interviews were also conducted to find out what factors influenced students in making mistakes. The results showed that the most mistakes made by students in working on algebraic thinking ability test questions were in the encoding indicator of 34%, the factors that influenced student errors included students not being used to working on problems systematically, students were also not used to writing answers completely, students did not understand the concept of algebra and did not understand the problem.